Physics-Based Simulation of Heat Load on Structures for Improving Construction Standards for Bushfire Prone Areas - Khan, Nazmul; Sutherland, Duncan; Wadhwani, Rahul; Moinuddin, Khalid (Frontiers in Mechanical Engineering, 2019)
Australian building standard AS 3959 provides mandatory requirements for the construction of buildings in bushfire prone areas in order to improve the resilience of the building to radiant heat, flame contact, burning embers, and a combination of these three bushfire attack forms. The construction requirements are standardised based on the bushfire attack level (BAL). BAL is based on empirical models which account for radiation heat load on structure. The prediction of the heat load on structure is a challenging task due to many influencing factors: weather conditions, moisture content, vegetation types and fuel loads. Moreover, the fire characteristics change dramatically with wind velocity leading to buoyancy or wind dominated fires that have different dominant heat transfer processes driving the propagation of the fire. The AS 3959 standard is developed with respect to a quasi-steady state model for bushfire propagation assuming a long straight line fire. The fundamental assumptions of the standard are not always valid in a bushfire propagation. In this study, physics based large-eddy simulations were conducted to estimate the heat load on a model structure. The simulation results are compared to the AS 3959 model; there is agreement between the model and the simulation, however, due to computational restrictions the simulations were conducted in a much narrower domain. Further simulations were conducted where wind velocity, fuel load, and relative humidity are varied independently and the simulated radiant heat flux upon the structure was found to be significantly greater than predicted by the AS 3959 model. The effect of the mode of fire propagation, either buoyancy-driven or wind dominated fires, is also investigated. For buoyancy dominated fires the radiation heat load on the structure is enhanced compared to the wind dominated fires. Finally, the potential of using physics based simulation to evaluate individual designs is discussed.